2018
DOI: 10.1111/acps.12994
|View full text |Cite
|
Sign up to set email alerts
|

ECT beyond unipolar major depression: systematic review and meta‐analysis of electroconvulsive therapy in bipolar depression

Abstract: ECT beyond unipolar major depression: systematic review and metaanalysis of electroconvulsive therapy in bipolar depression.Objective: In this systematic review and meta-analysis, the response, remission, and speed of response in adults with major depressive disorder (MDD) and bipolar disorder in depressive episode (BDD) receiving an acute course of electroconvulsive therapy (ECT) were quantitatively analyzed. Methods: Using the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines, 166… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
70
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 60 publications
5
70
0
2
Order By: Relevance
“…Patients can choose their treatment, but they cannot choose their condition. Even if, in contrast to the meta-analysis by Bahji et al, 1 such comparisons were based on evidence from randomized trials, the relative measure of outcomes in one patient population compared to another offers no information on the absolute benefits of the treatment in either population. Thus, one could theoretically compare two populations with different conditions where one is given a treatment that has no effect and arrive at a conclusion similar to that of Bahji et al 1 : that outcomes were superior in the treated group.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Patients can choose their treatment, but they cannot choose their condition. Even if, in contrast to the meta-analysis by Bahji et al, 1 such comparisons were based on evidence from randomized trials, the relative measure of outcomes in one patient population compared to another offers no information on the absolute benefits of the treatment in either population. Thus, one could theoretically compare two populations with different conditions where one is given a treatment that has no effect and arrive at a conclusion similar to that of Bahji et al 1 : that outcomes were superior in the treated group.…”
mentioning
confidence: 97%
“…On the basis of a meta-analysis that compared patients with unipolar depression against patients with bipolar depression who received electroconvulsive treatment (ECT), Bahji et al 1 concluded that their findings supported increased utilization of ECT in patients with treatment-refractory bipolar depression and urged for more clinicians to use ECT in both unipolar and bipolar depression. However, due to several methodological limitations in their meta-analysis their recommendations do not seem supported by the evidence.…”
mentioning
confidence: 99%
See 3 more Smart Citations